Empoderamiento académico de los estudiantes de secundaria del Colegio Rural Luz de la Esperanza por medio de la estrategia pedagógica integradora “Todos somos uno” - Tarazona Ariza, Silvia Andrea; Fajardo Rivera, Rubiela (Rastros Rostros, 2023)
The purpose of this article is to critically reflect on the benefits of the pedagogical and integrative strategy with a community approach called “We are all one”; which was thought of as a means to strengthen academic performance in three areas of knowledge in students of all secondary school grades (6th to 11th) of the rural school Luz de la Esperanza located in the municipality of Tona in the department of Santander in Colombia. The main objective of this proposal was the articulation of the actions developed by the educational community of this institution to facilitate the academic processes in a more effective way, optimizing the results of evaluation and school performance in the areas of Spanish language, mathematics, and English. The implementation of the proposal suggests the curricular redesign of the institution and the conscious and voluntary integration of the actors of the educational community for the benefit of the students since these shared practices promote their optimal academic performance.
Keywords: Empowerment; curricular design; pedagogical strategy; academic community; academic performance